2013
DOI: 10.1007/s12035-013-8492-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons

Abstract: In the present study, the role of heme oxygenase (HO)-1 in sodium arsenite (arsenite)-induced neurotoxicity was investigated using primary cultured cortical neurons. Incubation with arsenite was found to cause cell death of primary cultured cortical neurons in concentration- and time-dependent manners. Furthermore, arsenite induced caspase 3 activation and decreased procaspase 12 levels, indicating that apoptosis is involved in the arsenite-induced neurotoxicity. The oxidative mechanism underlying arsenite-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Arsenic ( As ) has been identified as inducer of heme oxygenase (HO)-1expression in many cells and tissues (Teng et al 2013; Li et al 2013). Consistent with these reports, we demonstrated that the induction of HO-1 protein expression was dose- and time-dependent in HK-2 cells after As exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic ( As ) has been identified as inducer of heme oxygenase (HO)-1expression in many cells and tissues (Teng et al 2013; Li et al 2013). Consistent with these reports, we demonstrated that the induction of HO-1 protein expression was dose- and time-dependent in HK-2 cells after As exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the induction of HO-1 by As is ROS dependent (Fan et al 2010; Teng et al 2013). Our previous data have demonstrated that As exposure elevated ROS production in HK-2 cells (Gong et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, HO-1 was recently reported as a harmful gene that mediated oxidative stress and apoptosis, particularly in neurons [18,[70][71][72]. The upregulation of HO-1 is a key event in the cascade leading to excessive mitochondrial iron deposition in oxidative challenged astroglia and promotes mitochondrial oxidation [23,24,26,27,34,73].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether HO-1 is harmful or helpful in AD has been debated for a long time in this research field [16]. HO activity has been shown to be neuroprotective or anti-oxidative stress in various models of neural injury and disease [17,18]. The overexpression of HO-1 in neurons appears to be relatively resistant to glutamate, H 2 O 2 and other damage, such as amyloid-␤-mediated oxidative damage in vitro and in vivo [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this notion, arsenics have been shown to induce oxidative stress, including free radical formation, glutathione depletion, lipid peroxidation, and mitochondrial impairment [5][6][7][8][9][10][11][12]. Antioxidative strategies have been suggested for arsenics-induced neurotoxicity [13][14][15][16][17][18][19][20][21]. Indeed, melatonin with antioxidative activities via direct scavenging free radicals, chelating metals, and enhancing antioxidative defensive enzymes has been used as a neuroprotective agent for decades [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%